Use of sequentially inoculation of Saccharomyces cerevisiae and Hanseniaspora uvarum strains isolated from honey by-products to improve and stabilize the quality of mead produced in Sicily. (October 2022) - Prestianni, Rosario; Matraxia, Michele; Naselli, Vincenzo; Pirrone, Antonino; Badalamenti, Natale; Ingrassia, Marzia; Gaglio, Raimondo; Settanni, Luca; Columba, Pietro; Maggio, Antonella; Bruno, Maurizio; Francesca, Nicola; et al.
Abstract: Mead is a beverage produced by alcoholic fermentation of honey-must. The starter yeasts that are commonly used for the alcoholic fermentation of honey-must are oenological Saccharomyces cerevisiae strains. The objective of the present work was, for the first time, to apply yeasts of honey by-products origin to evaluate the influences the taste-olfactory attributes of mead. For this purpose, three experimental productions were set up, which included: (i) single inoculation of S. cerevisiae ; (ii) single inoculation of Hanseniaspora uvarum ; (iii) sequential inoculation of H. uvarum / S. cerevisiae . Two control trials were performed, using a commercial strain of S. cerevisiae of oenological origin and a spontaneous fermentation. The results of the chemical parameters showed differences between the trials in terms of residual sugars, acetic acid, glycerol, ethanol and volatile organic compounds. Sensorial analysis also showed a high heterogeneity among trials. The attributes of sweetness, honey and floral were found in mead fermented with H. uvarum, whereas all meads obtained with S. cerevisiae were dry, balanced and without off-odors and off-flavours. The results obtained showed that the controlled application of conventional and non-conventional yeast strains isolated from honey by-products origin could be a promising approach to improve the quality of meads. Highlights: The strains SPF 21 of Saccharomyces cerevisiae was suitable for mead production. Hanseniaspora uvarum was used for the first time in mead fermentation. Sequential inoculum S. cerevisiae / H. uvarum increased glycerol content. Esters were found to be the VOCs present in the highest concentration. Sensory attributes of meads were influenced by strains and inoculation methods.